-3x+18=(13-10+4x-2)

Simple and best practice solution for -3x+18=(13-10+4x-2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3x+18=(13-10+4x-2) equation:



-3x+18=(13-10+4x-2)
We move all terms to the left:
-3x+18-((13-10+4x-2))=0
We add all the numbers together, and all the variables
-3x-((4x+1))+18=0
We calculate terms in parentheses: -((4x+1)), so:
(4x+1)
We get rid of parentheses
4x+1
Back to the equation:
-(4x+1)
We get rid of parentheses
-3x-4x-1+18=0
We add all the numbers together, and all the variables
-7x+17=0
We move all terms containing x to the left, all other terms to the right
-7x=-17
x=-17/-7
x=2+3/7

See similar equations:

| 11+13(x-2)=15x-2(x+4) | | x+(5/6x)=33 | | 21/2x=63 | | 101/2x=63 | | 7.4b=5 | | 2x^2+50=-116 | | 6x-4x=2x+6 | | 2z^2+50=~166 | | Y=-50+b | | -4|3x-5|=8 | | 6(0)-8y=-24 | | X-(x*0.05)=15634 | | −2(−x+4)+4x−3=−2(−x+4)+4x−3=  3131 | | (6+x)/2=x+4 | | 3/2t2=4 | | 2x+3(2x-5)+4=x+3(3x-2)-6 | | x2−19x+102=−x-6 | | (1/16)=8^(4x-2) | | 7x+40=(1+4x) | | 4*4*4*4*3*4*4*4*4*7*4*4*4*4*29*4*4*4*4*59=x | | 58x=765 | | x^2−14x+11=11 | | 3x+6(x+1)=3(x+1)+5 | | 2(3x-4)-4x=-42 | | 14-10x=X+36 | | 4x+6-x-2=4x+6-x | | 80-6x=32 | | 80-6x=33 | | 5x+4-10=34 | | X-(x*0.05)=21351.85 | | 5.5+x=25 | | 5/6x+1/3=5/2 |

Equations solver categories